PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MENGGUNAKAN MODEL PROBLEM BASED INSTRUCTION (PBI) PADA MATERI SUHU DAN KALOR DI KELAS VII SMP - Safira, Triyana; Islami, Nur; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning tools that developed in this research is science learning tools using the Problem Based Instruction (PBI) model on temperature and heat material in grade VII Junior High School. It consists of Lesson Plan, Student Worksheet, and Cognitive Evaluation Question. The purpose of this research is to produce valid physics learning tools using the Problem Based Instruction (PBI) model and suitable to improve the students cognitive ability on temperature and heat material in grade VII junior high school. This research is expected to be a reference for making innovative learning tools and can be used as a foundation in the teaching and learning process so that learning objective can be achieved. This type of research is Research and Development (R&D) using ADDIE model. This research in only limited to the development stage. The research instrument that used is the Lesson Plan validation assessment sheet, Student Worksheet, and Cognitive Evaluation Question which is used by the validator to assess the learning tools. Data analysis of this study is descriptive analysis, by calculating the validation score of each indicator of the learning tools. The result shows that the science learning device using the Problem Based Instruction (PBI) model is valid, with the mean overall score of the tools is 3.41 in high category. So it is proper to use in teaching temperature and heat material in grade VII junior high school.Key words: PBI model science learning tools, temperature and heat material.